Dairy farmers’ perception towards climate variability in Western dry region of India - KANT, KAMALA; SANKHALA, GOPAL; PRASAD, KAMTA; CHAKRAVARTY, RITU (The Indian Journal of Animal Sciences, 2015)
Perception is affected by factors such as social and cultural backgrounds, past experience, attitude, knowledge and information. The process of perception is crucial to understand human behaviour. Rural community may not be knowing the reasons of climate variations, but they righty analysed and felt its effects. Farmer perceptions are considered to be critical as a determinant and necessary precondition for adaptation. This paper analyses the perception of dairy farmers towards climate variability in 16 villages in Western dry region of India utilizing a descriptive research design. The majority of farmers surveyed exhibited a medium level of perception towards climate variability. Correlation test showed that education, social participation, experience in dairying, annual income, extension contact, mass media exposure and preparedness to act were correlated positively and significantly with perception level. Nine variables fitted in the regression model and explained 56.70% of the variation in the perception of dairy farmers.